Rise of circulating thrombopoietin following cardiothoracic surgery is potentiated in patients with coronary atherosclerosis: correlation with a preceding increase in levels of interleukin-6 - Cotton, James M.; Hong, Ying; Hawe, Emma; Mathur, Anthony; Humphries, Steve E.; Brown, Angie S.; Martin, John F.; Erusalimsky, Jorge D. (Thrombosis and Haemostasis, 2003)
Thrombopoietin (TPO) is the major regulator of platelet production. Plasma levels of TPO are thought to be regulated by its binding to platelets and megakaryocytes. Here we have used a model of cardiac surgery with cardiopulmonary bypass (CBP) to test the possibility that changes in TPO levels are influenced by the presence of coronary artery disease (CAD) and by changes in interleukin-6 (IL-6). After surgery patients with CAD (n = 22) or with normal coronary arteries (n = 11) showed a significant thrombocytopaenia followed by a reactive thrombocytosis. The platelet recovery was preceded by a significant rise in TPO (from 62.6 ± 9.4 pg/ml at baseline to 129.2 ± 19 pg/ml at 60 h, P <0.001), which in turn was preceded by, and was positively correlated with, a marked increase in circulating IL-6 (from 1.5 ± 0.3 pg/ml at baseline to 269.3 ± 30.6 pg/ml at 3-12 h, P <0.001). The rise of both IL-6 and TPO was significantly larger in patients with CAD. No correlation was found between the post-operative drop in platelet mass and changes in either the TPO or IL-6 levels. These findings suggest that in man circulating TPO levels, besides being controlled by changes in platelet mass, are influenced by inflammatory processes, including the presence of coronary atherosclerosis.
Keywords: Atherosclerosis; thrombopoietin; interleukin-6; platelets; cardiovascular surgery